Energy calculations & problem solving sourcebook : a practical guide for the Certified Energy Manager Exam - Dunning, Scott; Katz, Larry S. (The Fairmont Press, Inc., 2017)
This book is designed to serve as a practical guide to energy professionals preparing to take the Association of Energy Engineers (AEE) Certified Energy Manager (CEM®) examination.